(untitled) (MAUSAM, 2010)
A very severe cyclonic storm “Mala” (25-29 April 2006) developed over south east Bay of Bengal. Initially the system moved northwestwards while intensifying into the stage of cyclonic storm during 25-26th April 2006. It then recurved and moved in a north-northeasterly direction and crossed Arakan coast as a very severe cyclonic storm on 29th April, 2006 causing loss of life and property over the region. The unique features associated with this system was the continuous intensification after the recurvature.Various diagnostic features associated with intensification and movement of this system have been analysed and discussed. The study highlights the use of different dynamic and thermodynamic parameters as precursors for prediction of intensity and movement of the system. It also discusses the interaction of very severe cyclonic storm Mala with a vortex over the south Indian Ocean.